The implementing the Role of the Police in Preventing Gambling Crimes - Beny Fajar Sanjaya; Amin Purnawan; Aryani Witasari (Universitas Islam Sultan Agung, 2022)
The objectives to be achieved in this study are to find out the factors causing the rampant gambling in the Kudus region, to determine the implementation of the role of the Kudus Resort Police in preventing gambling crimes and to find out what obstacles and solutions are in implementing the role of the Kudus Resort Police in preventing gambling crimes? The research method used in this study is a juridical-sociological approach. The data analysis method used in this study is qualitative analysis, which is a way of analyzing research results that produces analytical descriptive data. The conclusions in this study are the factors that cause the rampant gambling in the Kudus area: They, especially the small and poor people, feel uncertain about the future, and are not sure that with reasonable business results they can get balanced results They feel they do not get protection and The role of the Police in Combating Gambling in Kudus is extraordinary, so that the Kudus Polres can be said as one of the Polres that consistently eradicates Gambling indiscriminately. Kudus Police and Efforts: Obstacles originating from the community/outside the police. Obstacles that come from within the police.